Analysis of the Effect of Marketing Mix 9p on Revisit Interest of Outpatient Patients at Metta Medika Hospital in Padangsidimpuan City - Rizkitha Martono Putri; A Rohendi; Achmad Dheni Suwardhani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Hospital marketing is carried out to fulfill patient needs and desires and generate profits for the hospital. A good marketing strategy requires a marketing mix method to achieve health service goals. The marketing mix is a hospital's main business closely related to patient behavior in utilizing services. The intention to revisit is influenced by patient perceptions of the marketing mix. This study aims to analyze the effect of the 9P marketing mix on the intention to revisit outpatients at Metta Medika Hospital, Padangsidimpuan City. The study uses quantitative methods with a sample of 340 outpatients selected using incidental sampling. Data collection uses questionnaires with a Likert scale. Data processing uses the Classical Assumption Test and multiple linear regression analysis with Statistical Package For The Social Science (SPSS). Partial research results show that process (p=0.029), physical evidence (p=0.000), people (p=0.007), and public relations (p=0.000) variables significantly influence revisit intentions. Meanwhile, product, price, place, promotion, and power variables do not have a significant effect. Simultaneously, all 9P marketing mix variables have a significant effect (F=28.814; p=0.000) with an R Square value of 0.440, indicating 44% of the variation in revisit intention can be explained by the 9P marketing mix variables.